Study of early changes in intraocular pressure following phacoemulsification - Shu, Chaw Lee; Kueh, Adeline; Chien, Joo Lim; Ching, Wei Lim; Siew, Leng Ting (Malaysian Medical Association, 2018)
: To evaluate early postoperative changes in intraocular pressure (IOP) following phacoemulsification and intraocular lens (IOL) implantation. Method: This retrospective and observational study included 100 patients with normal IOP underwent uneventful standard phacoemulsification procedure for senile cataracts at Sarawak General Hospital over a period of six months from July 2017 to December 2017. Patient's data were retrieved from Eye Clinic records. All patients were checked for IOP with Goldmann tonometry during pre-operative assessment and one month postoperatively. Patients with pre-existing IOP related ocular disease or intraocular surgery were excluded. Effects of age, gender, comorbidity of diabetes mellitus and hypertension, eye laterality, ocular axial length and pre-operative IOP on post-operative IOP reduction were analysed. Results: Phacoemulsification was found to reduce IOP by mean of 1.07 mmHg, which was statistically significant (P < 0.001). A larger IOP reduction was seen in cases with a higher pre-operative IOP (P < 0.001). No statistically significant differences were identified in age, gender, comorbidity of diabetes mellitus or hypertension, eye laterality, and ocular axial length in correlation with postoperative IOP reduction (P > 0.05). Conclusion: Phacoemulsification had a significant IOP-lowering effect in normal subjects, in particular in higher pre-operative IOP. There was no correlation between age, gender, comorbidity of diabetes mellitus or hypertension, eye laterality, and ocular axial length to IOP reduction following hacoemulsification.